Clay chips and beads capture in situ barley root microbiota and facilitate in vitro long-term preservation of microbial strains. Issue 7 (31st May 2022) - Abdelfadil, Mohamed R; Taha, Manar H; El-Hadidi, Mohamed; Hamza, Mervat A; Youssef, Hanan H; Khalil, Mohab; Henawy, Ahmed R; Nemr, Rahma A; Elsawey, Hend; Tchuisseu Tchakounte, Gylaine Vanissa; Abbas, Mohamed; Youssef, Gehan H; et al.
Abstract: Capturing the diverse microbiota from healthy and/or stress resilient plants for further preservation and transfer to unproductive and pathogen overloaded soils, might be a tool to restore disturbed plant–microbe interactions. Here, we introduce Aswan Pink Clay as a low-cost technology for capturing and storing the living root microbiota. Clay chips were incorporated into the growth milieu of barley plants and developed under gnotobiotic conditions, to capture and host the rhizospheric microbiota. Afterward, it was tested by both a culture-independent (16S rRNA gene metabarcoding) and -dependent approach. Both methods revealed no significant differences between roots and adjacent clay chips in regard total abundance and structure of the present microbiota. Clay shaped as beads adequately supported the long-term preservation of viable pure isolates of typical rhizospheric microbes, i.e. Bacillus circulans, Klebsiella oxytoca, Sinorhizobium meliloti, and Saccharomyces sp., up to 11 months stored at −20°C, 4°C,  and ambient temperature. The used clay chips and beads have the capacity to capture the root microbiota and to long-term preserve pure isolates. Hence, the developed approach is qualified to build on it a comprehensive strategy to transfer and store complex and living environmental microbiota of rhizosphere toward biotechnological application in sustainable plant production and environmental rehabilitation. Abstract : This study evaluates the ability of clay chips and beads as a practical and cheap methodology to capture the microbiota from barley roots and preserve pure isolates up to 11 months.